Ambiguity Aversion and the Term Structure of Interest Rates - Gagliardini, Patrick; Porchia, Paolo; Trojani, Fabio (Review of Financial Studies, 2009)
This paper studies the term structure implications of a simple structural model in which the representative agent displays ambiguity aversion, modeled by Multiple Priors Recursive Utility. Bond excess returns reflect a premium for ambiguity, which is observationally distinct from the risk premium of affine yield curve models. The ambiguity premium can be large even in the simplest log-utility setting and is also nonzero for stochastic factors that have a zero risk premium. A calibrated low-dimensional two-factor model with ambiguity is able to reproduce the deviations from the expectations hypothesis documented in the literature, without modifying in a substantial way the nonlinear mean-reversion dynamics of the short interest rate. Moreover, the model does not imply any apparent trade-off between fitting the first and second moments of the yield curve. The Author 2008. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oxfordjournals.org., Oxford University Press.